Adaptive Classroom Berbasis IoT (Internet Of Things), Saklar Lampu Berdasarkan Keberadaan Seseorang Dan Intensitas Cahaya - Hendra Oji Pratama; I Gde Putu Wirarama Wedashwara Wirawan; Ariyan Zubaidi (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2020)
A switch is a device for disconnecting or connecting electricity, usually used on lights. The Informatics Engineering Study Program (PSTI) of the Faculty of Engineering of the University of Mataram (UNRAM) has several classrooms with light switches controlled by manual switches. Problems occur when classroom users do not turn off class lights after use or when the room has sufficient lighting from outside. The solution is by implementing an automatic control system based on Internet of Things (IoT) that uses several sensors as a trigger switch. The monitoring system created can display light intensity data, motion status, and lamp status in real time obtained from the electronic circuit of the system via the MQTT protocol. Based on the test scheme carried out, the system created can perform lamp management based on the conditions received. MOS testing produces value 4.58 from scale 5 shows that the system is feasible to use.